BODY MASS INDEX AND EFFECTS DURING KAYAKING - Milomir Trivun; Jovica Tošić; Simo Vuković; Goran Pašić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Comparison of the results was performed among the sample of 55 male students of second year from the Faculty of Physical Education and Sports at the University of East Sarajevo, School Year 2009/2010, chronologically aged 23 years ±6 months. Comparison of the results was done at the following parameters: BMI (Body Mass Index) at one side and variables of kayaking in natural conditions in 200 meters. The results obtained both with the measures of central tendency (minimum, maximum, mean value) and with multivariate regression analysis indicated a large dispersion of the results which were related to variable body mass index, and their impact on the result success in kayaking in natural conditions, stationed at Camp Tjentište.